Principal Leadership in Integrated Islamic Early Childhood Education - Mayasari, Mayasari; Aslamiah, Aslamiah; Novitawati, Novitawati (Universitas Pahlawan Tuanku Tambusai, 2025)
The management and implementation of education in schools is very necessary for good coordination and cooperation between school personnel, principals, teachers, other education personnel, and with parents or school committees and school supervisors to realize the goals that have been set with the coordination of all parties to this school, so that the ideals of quality education can be achieved as they should be (Ikhsandi, 2021). In order for schools to achieve their goals effectively and efficiently, school principals must carry out managerial functions such as planning, organizing, directing, motivating, implementing, organizing, control, evaluation and innovation. A good principal is expected to shape the implementation of learning carried out by good teachers. If learning at school is good, it will certainly result in good achievements of children and teachers. With this in mind, a school principal is needed who is able to lead and exert influence effectively in carrying out his obligations. The growth of such quality Islamic schools is undoubtedly inspired by the Islamization of formal education. Among the Islamic schools that are massively spread in various regions in Indonesia are Integrated Islamic Schools (SIT). Quality schools are able to improve and create an effective and quality educational environment under the leadership of school principals who have expectations in improving the quality of learning, inspiring and motivating educators and educators, being able to increase partnerships, support resource management and be able to face educational challenges.